2012
DOI: 10.1177/2319510x1200800102
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary versus Mandatory EMS Implementation: Management Awareness in EMS-certified Firms

Abstract: This article examines the implications of turning a voluntary management instrument such as Environmental Management Systems (EMSs) into a compulsory one. Environmental Management Systems are voluntary operational management tools that can help firms to both reduce their impact on the natural environment and gain financial benefits (win-win strategy). However, some countries have lately enacted environmental regulations to pressurise firms to adopt EMSs. To this end, the findings of the previous studies have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…The perception of financial incentives was recognized as being more important than technical incentives; however, the result did not show a significant value, which suggests that the scheme is not effective in amplifying the relationship between the internal drivers and the intention to adopt an EMS. This is consistent with Nikolaou, Evangelinos, and Emmanouil (2012), who found that the provision of financial incentives consistently fails to deliver an effective compliance. Engel, Pagiola, and Wunder (2008) argue that the scheme can create a perverse incentive as it will increase firm dependency on financial assistance, rather than relying on their internal motivation.…”
Section: Organizational-institutional Nexussupporting
confidence: 89%
“…The perception of financial incentives was recognized as being more important than technical incentives; however, the result did not show a significant value, which suggests that the scheme is not effective in amplifying the relationship between the internal drivers and the intention to adopt an EMS. This is consistent with Nikolaou, Evangelinos, and Emmanouil (2012), who found that the provision of financial incentives consistently fails to deliver an effective compliance. Engel, Pagiola, and Wunder (2008) argue that the scheme can create a perverse incentive as it will increase firm dependency on financial assistance, rather than relying on their internal motivation.…”
Section: Organizational-institutional Nexussupporting
confidence: 89%
“…The findings from this study suggest there is an important role to play for government, F&B industry bodies, and educational institutions in promoting the adoption of EMS to the industry and public as a whole. A strategy to promote EMS adoption could take the form of 361 mandatory EMS requirements through legislation (Nikolaou et al, 2012) and to encourage 362 voluntary adoption supported by capacity building exercises via financial as well as technical 363 incentives (Zeng et al, 2005). This initiative could support improved inclusivity of Malaysian 364 F&B products in the global food market (Neumayer and Perkins, 2004).…”
Section: Future Steps For Ems Adoption In Malaysia 358mentioning
confidence: 99%
“…The academic debate has recently focused on EMS internalisation considering especially the barriers that makes EMSs difficult to be implemented (Loizia et al, 2018;Voukkali et al, 2017). Scholars initially believed that ISO14001 and EMAS were uniformly adopted by organisations (Nikolaou et al, 2012;Zorpas, 2010), but some have demonstrated that by fully integrating the requirements of the standards, organisations can achieve better environmental performance (Testa et al, 2018). Testa et al (2018) used the EMS level of maturity as a proxy of the level of internalisation, thus considering all of the EMS requirements to assess the extent of internalisation.…”
Section: Introductionmentioning
confidence: 99%